Integrative transcriptomic and metabolomic analysis reveals the mechanism of GABA and melatonin co-treatment enhancing flavonoid and alkaloid biosynthesis in Dendrobium officinale protocorm-like bodies - Mingfeng Liu; Yu Shao; Yitian Chen; Xiuying Xia; Zhilong Xiu (Food Bioscience, 2026)

Pea protein-steviol glycosides complexes: Fabrication, characterization and evaluation for the emulsifying capacity - Wen Wang; Jingyu Xia; Min Zhang; Enqi Pei; Cuina Wang; Mingfeng Xu; Rongrong Yu (Food Chemistry, 2026)

High production of biomass and bioactive compounds by Dendrobium officinale protocorm-like bodies induced by exogenous additives - Mingfeng Liu; Xiuying Xia; Jianying Dai; Zhilong Xiu (Food Bioscience, 2025)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Antisense oligonucleotide technology can be used to investigate a circular but not linear RNA-mediated function for its encoded gene locus - Zhenxing Song; Ruirui Jia; Mingfeng Tang; Fei Xia; Haiyang Xu; Zhengguo Li; Chuan Huang (Science China Life Sciences, 2021)

Improved robust tensor principal component analysis for accelerating dynamic MR imaging reconstruction - Mingfeng Jiang; Qiannan Shen; Yang Li; Xiaocheng Yang; Jucheng Zhang; Yaming Wang; Ling Xia (Medical & Biological Engineering & Computing, 2020)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)